Tesis, Antitesis, dan Sintesis Terhadap Agama - Frederikus Fios (Bina Nusantara University, 2014)
From the beginning until now, religion has always been a paradoxical term. Religion has become an ambiguous term because it has both thesis and antithesis that are closely inherent. The thesis is that religion is positive strength striving for virtue, salvation, prosperity, happiness, and peace in the reality of human society globally and locally. On the other hand, religion also appears as negative force to be the antithesis of the religion itself. Problems rise on the religion lie not in the thesis but in the antithesis because thesis and antithesis are always accompanying the dynamics of religion in society reality. So that, it needs a